Urgent endoscopic retrograde cholangiopancreatography with sphincterotomy versus conservative treatment in predicted severe acute gallstone pancreatitis (APEC): a multicentre randomised controlled trial. Issue 10245 (18th July 2020) - Schepers, Nicolien J; Hallensleben, Nora D L; Besselink, Marc G; Anten, Marie-Paule G F; Bollen, Thomas L; da Costa, David W; van Delft, Foke; van Dijk, Sven M; van Dullemen, Hendrik M; Dijkgraaf, Marcel G W; van Eijck, Casper H J; Erkelens, G Willemien; et al.
Summary: Background: It remains unclear whether urgent endoscopic retrograde cholangiopancreatography (ERCP) with biliary sphincterotomy improves the outcome of patients with gallstone pancreatitis without concomitant cholangitis. We did a randomised trial to compare urgent ERCP with sphincterotomy versus conservative treatment in patients with predicted severe acute gallstone pancreatitis. Methods: In this multicentre, parallel-group, assessor-masked, randomised controlled superiority trial, patients with predicted severe (Acute Physiology and Chronic Health Evaluation II score ≥8, Imrie score ≥3, or C-reactive protein concentration >150 mg/L) gallstone pancreatitis without cholangitis were assessed for eligibility in 26 hospitals in the Netherlands. Patients were randomly assigned (1:1) by a web-based randomisation module with randomly varying block sizes to urgent ERCP with sphincterotomy (within 24 h after hospital presentation) or conservative treatment. The primary endpoint was a composite of mortality or major complications (new-onset persistent organ failure, cholangitis, bacteraemia, pneumonia, pancreatic necrosis, or pancreatic insufficiency) within 6 months of randomisation. Analysis was by intention to treat. This trial is registered with the ISRCTN registry, ISRCTN97372133. Findings: Between Feb 28, 2013, and March 1, 2017, 232 patients were randomly assigned to urgent ERCP with sphincterotomy (n=118) or conservative treatment (n=114). One patient from each group was excluded from the final analysis because of cholangitis (urgent ERCP group) and chronic pancreatitis (conservative treatment group) at admission. The primary endpoint occurred in 45 (38%) of 117 patients in the urgent ERCP group and in 50 (44%) of 113 patients in the conservative treatment group (risk ratio [RR] 0·87, 95% CI 0·64–1·18; p=0·37). No relevant differences in the individual components of the primary endpoint were recorded between groups, apart from the occurrence of cholangitis (two [2%] of 117 in the urgent ERCP group vs 11 [10%] of 113 in the conservative treatment group; RR 0·18, 95% CI 0·04–0·78; p=0·010). Adverse events were reported in 87 (74%) of 118 patients in the urgent ERCP group versus 91 (80%) of 114 patients in the conservative treatment group. Interpretation: In patients with predicted severe gallstone pancreatitis but without cholangitis, urgent ERCP with sphincterotomy did not reduce the composite endpoint of major complications or mortality, compared with conservative treatment. Our findings support a conservative strategy in patients with predicted severe acute gallstone pancreatitis with an ERCP indicated only in patients with cholangitis or persistent cholestasis. Funding: The Netherlands Organization for Health Research and Development, Fonds NutsOhra, and the Dutch Patient Organization for Pancreatic Diseases.